Allah speaks to the prophet musa - Khan, Saniyasnain (Goodword Kidz Place of publication not identified, 2003)
"Allah Speaks to the Prophet Musa" is a children's story that recounts the powerful encounter between Prophet Musa (Moses) and Allah, where Musa receives divine guidance and wisdom, emphasizing the importance of faith and obedience to God's commands.